Koncepcja zastosowania technologii światłowodowej w geodezyjnym monitoringu obiektów inżynierskich = An application concept of the fibre-optical technology in geodetic monitoring of engineering objects - Karsznia, Krzysztof; Podawca, Konrad (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Monitoring of structures and other different field objects undoubtedly belongs to the main issues of modern engineering. The use of technologies making it possible to implement structural monitoring makes it possible to build an integrated risk management approach combining instrumental solutions with geoinformation systems.
Keywords: monitoring geodezyjny; monitoring fizykalny; systemy geoinformacyjne; baza danych; geodetic monitoring; physical monitoring; geoinformation systems; database